Housing law and policy - Cowan, David (David S.) (Cambridge, UK : Cambridge University Press, 2011)
'An innovative and timely guide to housing law that integrates the disciplines of law and public policy so that readers see how the subject fits together - both the letter of the law and the way it is practised. The innovative three-part structure covers all the topics of a typical Housing Law module and it is written in a clear and conversational style, with a wide range of source material to show how the law is created, interpreted and used in real life. Students are expertly guided through the complexities of housing law by a leading academic who has taught the subject for more than 20 years. Where relevant, chapters end with a section on'the future' that discusses proposed changes to the law and the impact of those changes. It also discusses the conceptual issues raised by the Human Rights Act'--
Locating housing law and policy -- Part I. Regulation of Housing Tenure -- Regulating ownership -- Regulating private renting -- Regulating local authority housing -- Regulating private registered providers -- Part II. Access to Housing -- Homelessness -- Allocation of social housing -- Eligibility -- Access to private rented sector -- Access to owner-occupation -- Part III. Rights and responsibilities -- Security of tenure -- Harassment and unlawful eviction -- Property state and condition -- Arrears -- Anti-social behaviour -- Mandatory possession proceedings.
Includes bibliographical references (p. [411]-443) and index.
Keywords: Housing -- Law and legislation -- United Kingdom; Rent control -- United Kingdom; Landlord and tenant -- United Kingdom; Homeless persons -- Legal status, laws, etc. -- United Kingdom; Human rights -- United Kingdom